Dampak Pengelolaan Sampah Rumah Tangga terhadap Kesehatan Lingkungan di Permukiman Padat di Kelurahan Kekalik Jaya, Mataram - Hariati, Juanita (Gema Cendekia Institute, 2025)
The problem of household waste management in densely populated areas is a crucial issue that has a direct impact on environmental and public health. This study aims to analyze the relationship between household waste management systems and environmental health conditions in Kekalik Jaya Village, Mataram City. The study used a quantitative approach with a descriptive-analytical design. Data were collected through field observations, questionnaires, and interviews with 100 heads of families selected by purposive sampling. The results showed that most households (65%) had not implemented waste sorting, and 42% still disposed of waste in inappropriate places, such as gutters or empty land. This condition was significantly correlated with the high incidence of environmental-based diseases such as diarrhea, ARI, and skin diseases. In addition, the lack of environmental education and limited waste management facilities also worsened the quality of environmental health in the area. This study recommends the need for policy interventions and community empowerment programs in more effective and sustainable waste management.